Electromechnical delay of the hamstrings and its significance for the analysis and optimisation of sprint running - Jöllenbeck, T.
The established EMD values for the hamstrings were 24 ms+/- 7 ms. These results are in accordance with those values (23 ms) received by Hahn (192) - under the same experimental conditions - for MIVCs of the hamstrings with a visual method of evaluation. Surprinsingly the values of both studies are about 25% smaller than the shortest EMD values of the leg extensors obtained under similar conditions in the above mentioned studies.